Time spent on health‐related activities by senior Australians with chronic diseases: what is the role of multimorbidity and comorbidity? - M. Mofizul Islam; Ian S. McRae; Laurann Yen; Tanisha Jowsey; Jose M. Valderas (Elsevier, 2015)
Abstract Objective: To examine the effect of various morbidity clusters of chronic diseases on health‐related time use and to explore factors associated with heavy time burden (more than 30 hours/month) of health‐related activities. Methods: Using a national survey, data were collected from 2,540 senior Australians. Natural clusters were identified using cluster analysis and clinical clusters using clinical expert opinion. We undertook a set of linear regressions to model people's time use, and logistic regressions to model heavy time burden. Results: Time use increases with the number of chronic diseases. Six of the 12 diseases are significantly associated with higher time use, with the highest effect for diabetes followed by depression; 18% reported a heavy time burden, with diabetes again being the most significant disease. Clusters and dominant comorbid groupings do not contribute to predicting time use or time burden. Conclusions: Total number of diseases and specific diseases are useful determinants of time use and heavy time burden. Dominant groupings and disease clusters do not predict time use. Implications: In considering time demands on patients and the need for care co‐ordination, care providers need to be aware of how many and what specific diseases the patient faces.